Strategi Fleksibilitas Organisasi dalam Upaya Mempertahankan Kemampuan Fisik di Masa Pandemi Covid-19 Pada Pegawai Kantor Kementerian Agama Kota Surabaya - Anggraini Frida Ardhani; Airlangga Bramayudha (Journal of Islamic Management, 2021)
Organizational flexibility strategy is a method that is used when the main way or the general way used by an organization to change due to other factors. This study discusses the flexibility strategy used by the Surabaya City Ministry of Religion Office in dealing with the Covid-19 pandemic. The purpose of this study is to find out how the flexibility strategy is used and whether there is a difference with the application of self-protection applied by the whole community. Researchers used qualitative research methods, descriptive approach, data collection techniques by means of interviews, documentation, and observation. Data analysis techniques started from data transcription, interview coding, topic categorization, and data analysis. The data validation technique uses participation extension and data triangulation. The results of this study explain that the employees of the ministry of religion in the city of Surabaya apply the 3M health protocol as their flexibility strategy in carrying out work tasks. This government agency also implemented a Work From Home and Work From Office work system in rotation at the beginning of the COVID-19 pandemic and in the New Normal era implemented a full work system in the office